Psychodynamic approaches to behavioral change - Busch, Fredric N., 1958- (American Psychiatric Association Publishing, 2019)
This guide demonstrates how, rather than being at odds with psychoanalytic treatments, targeting behavioral change can be part of the development and employment of psychodynamic therapy and can be used to enhance self-understanding.